The Impact of Conflict and Political Instability on Banking Crises in Developing Countries - Compaore, Ali (IMF Working Papers; Working Paper, 2020)
While there is an extensive literature examining the economic impact of conflict and political instability, surprisingly there have been few studies on their impact on the probability of banking crises. This paper therefore investigates whether rising conflict and political instability globally over the past several decades led to increased occurrence of banking crises in developing countries. The paper provides strong evidence that conflicts and political instability are indeed associated with higher probability of systemic banking crises. Unsurprisingly, the duration of a conflict is positively associated with rising probability of a banking crisis. Interestingly, the paper also finds that conflicts and political instability in one country can have negative spillover effects on neighboring countries' banking systems. The paper provides evidence that the primary channel of transmission is the occurrence of fiscal crises following a conflict or political instability.